Force Transmission Between the Gastrocnemius and Soleus Sub-Tendons of the Achilles Tendon in Rat - Gains, Connor C.; Correia, Janaina C.; Baan, Guus C.; Noort, Wendy; Screen, Hazel R. C.; Maas, Huub (Frontiers in Bioengineering and Biotechnology, 2020)
The Achilles tendon (AT) is comprised of three distinct sub-tendons bound together by inter-subtendon matrix (ISTM). The interactions between sub-tendons will have important implications for AT function. The aim of this study was to investigate the extent to which the ISTM facilitates relative sliding between sub-tendons, and serves as a pathway for force transmission between the gastrocnemius (GAS) and soleus (SOL) sub-tendons of the rat AT. In this study, Achilles tendons were harvested from Wistar rats, and the mechanical properties and composition of the ISTM were explored. To determine force transmission between sub-tendons, the proximal and distal ends of the GAS and SOL sub-tendons were secured, and the forces at each of these locations were measured during proximal loading of the GAS. To determine the ISTM mechanical properties, only the proximal GAS and distal SOL were secured, and the ISTM was loaded in shear. Finally, for compositional analysis, histological examination assessed the distribution of matrix proteins throughout sub-tendons and the ISTM. The results revealed distinct differences between the forces at the proximal and distal ends of both sub-tendons when proximal loading was applied to the GAS, indicating force transmission between GAS and SOL sub-tendons. ISTM tests demonstrated an extended initial low stiffness toe region to enable some sub-tendon sliding, coupled with high stiffness linear region such that force transmission between sub-tendons is ensured. Histological data demonstrate an enrichment of proteins in the ISTM. We conclude that the ISTM composition and mechanical properties are specialised to allow some independent sub-tendon movement, whilst still ensuring capacity for force transmission between the sub-tendons of the AT.